Половецкий кобызчи - Гершкович, Я.П. (Степи Европы в эпоху средневековья, 2012)
In 1984 in Polovets burial 1 of barrow 4 near Kirovo village of Berislav region of Kherson province a set of well-preserved and diverse wooden objects which included a sleigh-coffin and a kobyz-like bowed musical instrument was found. The instrument consists of a boat-shaped scoop and a long fingerboard, a fingerboard head and a lath connecting them; inside at the scoop basis there was a yoke-shaped tailpiece with three cuts for strings. In a scoop body there were three sound holes of different diameter. The articles of similar type were found in the layers of the 11th-15th cc. Velikii Novgorod and partly (i.e. similar by separate details) of Staraia Russa, though with a number of essential constructive differences between them. In Western Europe there were stringed musical instruments related to kobyz and gudok - rebec, fidula or fidel. These “brothers” of a kobyz are considered as “great-grandfathers" of a violin. Later the name kobyz/kobuz was transferred onto the Ukrainian lute-like plucked string musical instrument, kobza.